The Kaptol Group and the Požega Valley - Potrebica, Hrvoje (Arheološki vestnik, 2019)
In the last two decades, most of the research related to the Kaptol Cultural group took place in the Požega Valley. The Iron Age communities of this area certainly belong to the Eastern Hallstatt Cultural Complex, but also had very strong ties with the south, which is particularly noticeable in the Late Hallstatt period. Numerous items discovered in the Požega Valley, including various types of weapons and elements of attire found here their farthest points of distribution within European framework. Preliminary geophysical investigations of the large and prosperous settlement with the long continuity point to highly organised, almost urban structure. The archaeobotanical methods have altered our perception and definition of the burial ritual of these communities. The LiDAR data indicate a polycentric model of the community structure in the Požega Valley. Investigations of the site Bangradac allow a hypothesis that the Iron Age centres of the Požega Valley were created after the Late Bronze Age fortified settlements had been abandoned. The new settlements were established on the lower slopes, closer to the valley. The relationship between the so-called Kaptol Group and neighbouring regions has not yet been defined.